Iron-folic acid supplementation and its differentials among Nepalese women of reproductive age - Shrestha, Ira; Paudel, Puja; Joshi, Mili; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: Iron-folic acid (IFA) supplementations protect mothers and their infants against perinatal and maternal mortality. Ministry of health and population advises pregnant women and lactating mother to take IFA supplements everyday for certain period. However, not all women follow this. Methods: 2011 Nepal Demographic and Health Survey (NDHS) data was used. Dependent variable was created using women with last child born live in the last five years and taking at least 1 tablet/syrup of IFA and women not taking any tablet/syrup during the study period. Key background variables of women and their last child born during last five years were used as independent variables. Logistic regression was used to find the association between the dependent and independent variables without controlling (bi-variate) and controlling (multi-variate) for other factors during analysis. Results: About 60% of the women took/bought IFA supplements. Although bivariate analysis showed the effects of perceived child size and type of place of residence on maternal intake of IFA, multivariate analysis did not show this effect. However, mother’s age, residence at hill region, education level and wealth index showed their effect on maternal IFA supplements intake in both bivariate and multivariate analysis. Conclusion: The mothers from Dalit, Janjati and other marginalized group, living in hill region, with no education and higher age were less likely to take IFA supplements. Therefore, such groups should be counseled to increase the use of IFA.